2023
DOI: 10.1161/circinterventions.123.013080
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Improvement in TAVR Outcomes Over Time: Insights From the STS-ACC TVT Registry

Abstract: BACKGROUND: Over the past decade, there has been substantial improvement in outcomes after transcatheter aortic valve replacement. Many patient and procedural factors have also changed over that time, making it challenging to untangle the drivers of those improvements. METHODS: Among patients who underwent transcatheter aortic valve replacement from 2012 to 2018 within the Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…When comparing our mortality data to other real-world data, a study from Germany reported periprocedural mortality rates of 6.3% in period 2 and 4.3% in period 3 ( 21 ), and other TAVI registries had comparable results to ours ( 22 , 23 ). Although most registries depict improvements in periprocedural mortality and 1-year mortality, Arnold et al demonstrated that between 2012 and 2018, the most important factors contributing to short-term outcomes were device technology and procedural factors ( 24 ). A study conducted by our group also found that TA-TAVI was a predictor of periprocedural mortality ( 25 ), comprising almost half of the procedures in period 1.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing our mortality data to other real-world data, a study from Germany reported periprocedural mortality rates of 6.3% in period 2 and 4.3% in period 3 ( 21 ), and other TAVI registries had comparable results to ours ( 22 , 23 ). Although most registries depict improvements in periprocedural mortality and 1-year mortality, Arnold et al demonstrated that between 2012 and 2018, the most important factors contributing to short-term outcomes were device technology and procedural factors ( 24 ). A study conducted by our group also found that TA-TAVI was a predictor of periprocedural mortality ( 25 ), comprising almost half of the procedures in period 1.…”
Section: Discussionmentioning
confidence: 99%
“… 6–8 In addition, ongoing improvements in devices and techniques also decreased the composite adverse events and mortality. 9 …”
Section: Introductionmentioning
confidence: 99%
“… 22–27 Owing to significant technological advancements and increased operator experience, rates of TAVR-associated AKI and stroke have slightly declined over time. 9 28 However, the incidence of TAVR-associated AKI remains at 10.5% to 11.5% in the USA and 6.8% in Asia. 9 29 On the other side, the incidence of stroke is approximately 3–5%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations